2002
DOI: 10.3184/147020602783698421
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Aetiology and Pathology of Leg Weakness in Broilers in Relation to Welfare

Abstract: Leg disorders in broilers are a major economic and welfare problem. The aetiology of many disorders is complex but includes genetics, growth rate (due to feed restriction or lighting regime), feed conversion efficiency and body conformation, exercise, circadian rhythms, nutrition and stocking density. These categories are not mutually exclusive as one aetiological factor may affect another. Many studies of leg disorders fail to identify the specific pathological condition underlying the observed lameness. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
213
3
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(234 citation statements)
references
References 297 publications
(694 reference statements)
4
213
3
8
Order By: Relevance
“…Further investigation into the aetiology is required, as infectious and degenerative causes of leg weakness such as bacterial chondronecrosis with osteomyelitis (femoral head necrosis) and/or tibial dyschondroplasia (TD) could be a causative factor. Tibial dyschondroplasia is a common lesion seen in broiler leg bones (Bradshaw et al, 2002). It is characterised by an abnormal cartilage mass in the metaphyseal region below the growth plate (Pompeu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation into the aetiology is required, as infectious and degenerative causes of leg weakness such as bacterial chondronecrosis with osteomyelitis (femoral head necrosis) and/or tibial dyschondroplasia (TD) could be a causative factor. Tibial dyschondroplasia is a common lesion seen in broiler leg bones (Bradshaw et al, 2002). It is characterised by an abnormal cartilage mass in the metaphyseal region below the growth plate (Pompeu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by an abnormal cartilage mass in the metaphyseal region below the growth plate (Pompeu et al, 2012). The pathogenesis of TD is not well understood, however, nutrition may influence the incidence (Bradshaw et al, 2002). Studies by Kestin et al (1994) and Vestergaard and Sanotra (1999) found that birds with TD had higher lameness scores and defect gaits.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive breast muscle accumulation combined with an inadequate skeletal development, gender, genetics, feeding, the composition of food, the incubation period, infectious diseases, environmental stress factors, maintenance and management factors affect the frequency and severity of leg problems (Bradshaw et al, 2002;Oviedo-Rondón et al, 2006a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the non-infectious disorders in poultry such as tibial dyschondroplasia and tarsal varus-valgus angulations result in abnormal gait and even lameness (Bradshaw et al, 2002;Mench, 2004). These disorders induce pain in some cases and impair birds' behavioural repertoire (McGeown et al, 1999; Danbury et al, 2000;Julian, 2004).…”
Section: Introductionmentioning
confidence: 99%